2012
DOI: 10.4314/sajas.v42i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of candidate genes associated with meat quality and disease resistance in indigenous and exotic pig breeds of Vietnam

Abstract: The objectives of this study were to analyse genotype distribution and sequence variations of candidate genes putatively associated with meat quality and disease resistance in exotic and indigenous Vietnamese pig breeds. For this purpose, 340 pigs from four indigenous and two exotic breeds were included in the analysis of the polymorphisms of the heart fatty-acid-binding protein (H-FABP), alpha 1 fucosyltransferase (FUT1), and bactericidal/permeability-increasing protein (BPI) genes by the sequencing and PCR-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The low frequency of A allele was also observed in Landrace and Yorkshire pigs in People's Republic of China (Ruan et al 2013). The AA genotype was absent in Asian local pigs breeds (Yan et al 2003;Bao et al 2008Bao et al , 2011Cuong et al 2012). In their work on exotic Yorkshire pigs under industrial condition in Vietnam, Cuong et al (2012) found the three genotypes and a frequency of AA estimated at 0.13.…”
Section: Genotypic and Allelic Distribution Of Fut1 Genementioning
confidence: 95%
See 2 more Smart Citations
“…The low frequency of A allele was also observed in Landrace and Yorkshire pigs in People's Republic of China (Ruan et al 2013). The AA genotype was absent in Asian local pigs breeds (Yan et al 2003;Bao et al 2008Bao et al , 2011Cuong et al 2012). In their work on exotic Yorkshire pigs under industrial condition in Vietnam, Cuong et al (2012) found the three genotypes and a frequency of AA estimated at 0.13.…”
Section: Genotypic and Allelic Distribution Of Fut1 Genementioning
confidence: 95%
“…Additionally, among surviving pigs, the resistant AA pigs demonstrated a 30% improvement of ADG compared with susceptible ones (Mellencamp et al 2008). In contrast, Huang et al (2008) reported that there was no effect of FUT1 gene on the growth performance of males in Duroc and Landrace breeds, and Cuong et al (2012) inferred that PWD has a negative relationship with growth rate. The slower average growth of pigs with diarrhea might either be due to the direct effect of the disease on the growth (i.e., piglets don't grow well at the beginning of the fattening period because they are sick) or to the effect of the resistant genotype which would also be favorable for the growth.…”
Section: Genotypic and Allelic Distribution Of Fut1 Genementioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, in the instances when piglets get disease the farmers hardly use medicine. As described by Cuong et al (2012) the efforts of crossbreeding and directional selection of indigenous pigs for lean percentage and high-growth rate in the Vietnamese pig herd has also resulted in a decrease in some economically important traits such as adaptation to the indigenous ecologies, meat quality (pork becomes tougher and is low in taste) and disease resistance.…”
Section: Pig Breeds Characteristics and Attributesmentioning
confidence: 99%
“…Regulation (EU) 2019/6 continues and strengthens the EU's fight against antimicrobial resistance by introducing a ban on the preventive use of antibiotics in groups of animals, a ban on the prophylactic use of antimicrobials in medicated feed, and restrictions on the use of antimicrobials as a control treatment to prevent a further spread of infection. The search for new ways to protect farm animals against diseases continues to arouse interest among scientists (7).…”
mentioning
confidence: 99%